Modele de interacţiune public-privat în furnizarea de servicii de angajare - Bădescu, Alina; Bădescu, Ciprian (Calitatea Vieții, 2008)
Succesful implementation of private – public interaction patterns regarding the providing of services is a challenge for nowadays organizations. The advance of globalization in the same time with increasing the permeabilities of organizational boundaries induces a change of value-added generating processes. Therefore, the production processes of goods and services, including the employment services, are not any longer limited to a single organization, but to some networks of interconnected organizations. These networks describe the new architecture of organizational processes, the organizations being nodes of these networks. Private – public interaction patterns in providing employment services are examples of rethinking the generating processes of such services. The implementation of such patterns may represent a beginning in crafting a new inter-organizational process regarding the employment services where public, as well as private actors, become nodes of a new network.